Poly[[[μ(3)-5-(pyridine-4-carboxamido)isophthalato]{μ(3)-5-[(pyridin-1-ium-4-yl)carbonylamino]isophthalato}neodymium(III)] dihydrate] - Deng, Yi-Fang (International Union of Crystallography, 2011)
In the title compound, {[Nd(C(14)H(9)N(2)O(5))(C(14)H(8)N(2)O(5))]·2H(2)O}(n), the Nd(III) atom is eight-coordinated as it is surrounded by eight carboxylate O atoms from six ligands in a distorted square-antiprismatic arrangement. The Nd(III) atoms are linked by HL (−) and L (2−) ligands [H(2) L is 5-(pyridine-4-carboxamido)isophthalic acid], forming a bilayer network. The layers are linked into a three-demensional network through N—H⋯O and O—H⋯O hydrogen bonds.